Automated chart filing on panoramic radiographs using deep learning. (December 2021) - Vinayahalingam, Shankeeth; Goey, Ru-shan; Kempers, Steven; Schoep, Julian; Cherici, Teo; Moin, David Anssari; Hanisch, Marcel
Abstract: Objective: The aim of this study is to automatically detect, segment and label teeth, crowns, fillings, root canal fillings, implants and root remnants on panoramic radiographs (PR(s)). Material and methods: As a reference, 2000 PR(s) were manually annotated and labeled. A deep-learning approach based on mask R-CNN with Resnet-50 in combination with a rule-based heuristic algorithm and a combinatorial search algorithm was trained and validated on 1800 PR(s). Subsquently, the trained algorithm was applied onto a test set consisting of 200 PR(s). F1 scores, as a measure of accuracy, were calculated to quantify the degree of similarity between the annotated ground-truth and the model predictions. The F1-score considers the harmonic mean of precison (positive predictive value) and recall (specificity). Results: The proposes method achieved F1 scores up to 0.993, 0.952 and 0.97 for detection, segmentation and labeling, respectivley. Conclusion: The proposed method forms a promising foundation for the further development of automatic chart filing on PR(s). Clinical significance: Deep learning may assist clinicians in summarizing the radiological findings on panoramic radiographs. The impact of using such models in clinical practice should be explored.